Review of superconducting transition-edge sensors for x-ray and gamma-ray spectroscopy - Ullom, Joel N; Bennett, Douglas A (Superconductor science & technology, 2015)
We present a review of emerging x-ray and gamma-ray spectrometers based on arrays of superconducting transition-edge sensors (TESs). Special attention will be given to recent progress in TES applications and in understanding TES physics.